Development of a Medical Care Terminal for Efficient Monitoring of Bedridden Subjects - Filipe Pereira; Vítor Carvalho; Filomena Soares; José Machado; Karolina Bezerra; Rui Silva; Demétrio Matos (Journal of Engineering)
This work is developed in the context of Ambient Assisted Living (AAL) and has as main objective the development of a mechatronic system that allows the care of bedridden patients with ongoing medical care handled by a single person. The developed Medical Care Terminal (MCT) improves autonomy in home care, safety, comfort, and hygiene of bedridden patients. The MCT has six biomedical sensors and four environmental sensors. Data acquisition and processing is performed using Arduino and LabVIEW platforms, respectively. The proposed solution has, as main feature, its adaptability to the patient needs. One of the MCT functionalities is the remote access to the patient data through the web. The caregiver may request help from a specialist who sends back information in real time to perform first aid assistance. This device has a flexible configuration allowing a fast and cheap reconfiguration according the specific needs of the patient. The proposed mechatronic system intends to meet the needs of bedridden patients improving their quality of life, health, safety, and comfort, while enabling the remote monitoring of the patients.